Determination of Some Chemical Constitutes of Oak Plants (Quercus spp) in the Mountain Oak Forest of Sulaimani Governorate - Ghafour, Noori Hassan; Aziz, Hoshyar Abdullah; Almolla, Ra'ad M. (Sulaimani Journal for Pure and Applied Sciences, 2010)
In this research work some chemical constitutes of Oak species were evaluated as a natural products in acorn, pericarp and cupules in the tree oak species (Quercus aegilops, Q. infectoria and Q. libani). The plant sample was collected in Khamza location district of Sulaimani Governorate during October- November 2004. The preliminary chemical detection for the composition in acorn, pericarp and cupules in each of the three species showed the presence of flavonoid, alkaloid, glycosides, tannins, phenolic compounds, resins, saponins, terpenes and steroid while the detection gave a negative results for alkaloids and saponins in acorn of the three test oak species. Total phenols conc. was determined by folin-cioculate method, while the total tannins were determined by radical diffusion method after extraction by dissolving samples in acetone (70%). Results indicated the existence of significant differences in total phenols and total tannins, conc. at 5% LSD among the fruit parts and species, indicating that pericarp of Q. aegilops contain the highest conc. of total phenols and total tannins, reaching (268.38 and 180.814 mg/g) respectively. Conc. of these compounds in cupules of Q. infectoria were the lowest reaching (171.49 and 51.802 mg/g) respectively. Ellagic acids were separated and determined using HPLC technique (high performance liquid chromatography), column (BD-C-18) type and mobile phase (0.01 M potassium phosphate buffer, methanol 70:30 v/v) after extraction by methanol (80%). The acorn of Q. infectoria contained the highest conc. of ellagic acid (5.168 mg/g) while cupules of Q. libani contained the lowest conc. of these compounds (1.310 mg/g).
Keywords: Various Oak species Quercus aegilops; Q infectoria and Q libani; acetoneand methanol extraction; HPLC; folincoiculate and radical diffusion method determination